PREPARATION AND TESTING ORBIT PLOT SOFTWARE USING LABVIEW PROGRAMMING LANGUAGE - PUTRA (NIM : 13104149); Pembimbing Utama : Dr. Ir. Zainal Abidin, RIESYA
Dynamics Laboratory of Mechanical Engineering ITB has developed several data acquisition softwares using LabVIEW programming language. The developed software capable of displaying various information of vibration, but not yet equipped with orbit plot. In fact, the orbit plot has additional information that does appear in vibration graphs either in frequency or time domain. In this research, a software has been developed with capability to draw an orbit plot. The Orbit Plot software has been developed using LabVIEW 8.0 programming language. This is done so that the software is compatible with softwares previously developed. The Orbit Plot software can read vibration data in txt format, so it can be used to process measurement data obtained from LabVIEW-based software or data obtained from other instrument. Several tests are carried out to determine the capability of the developed software. First test is performed by using artificial signals generated in the LabVIEW software. The test is conducted to determine whether the developed software work properly. Further test is performed by using data from real measurements. The data is obtained from the measurement by Ramdhan [1]. Based on the result, it can be concluded that the Orbit Plot software working properly. This is proved based on a comparison between graphs displayed on the Orbit Plot software with graphs created using Matlab. In addition, the software is also proved to be capable of reading data in txt format.